Family Support and Mother’s Occupation on The Accomplishment of Exclusive Breastfeeding - Beniqna Maharani Besmaya; Nopi Anggista Putri; Yuni Sulistiawati; Taufik Jamaan (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Exclusive breastfeeding is an intervention that can reduce the Infant Mortality Rate (IMR). Infants who received exclusive breastfeeding at the Penawar Jaya Health Center in 2019 were still low at 49%. The purpose of this study was to determine the relationship between family support and occupation with the success of exclusive breastfeeding for infants aged more than 7-12 months. This research was an analytic survey with a cross-sectional design. The research sample is 43 people. Data analysis with percentage and Chi-Square test. The results showed that mothers who received family support were 44.2%, working mothers were 67.4%, and those who gave exclusive breastfeeding were 51.2%. There is a relationship between family support and the success of exclusive breastfeeding (p-value = 0.048; OR = 4.333) and mother's work and the success of exclusive breastfeeding (p-value = 0.017 and OR = 6.967) in mothers who have babies aged more than 7-12 months in the Working Area of Penawar Jaya Health Center, Tulang Bawang Regency in 2021. Suggestions for working mothers are to be able to store expressed breast milk and continue to exclusively breastfeed their babies by involving family members to play a role in breastfeeding. Abstrack: Pemberian ASI ekslusif merupakan salah satu intervensi yang dapat menurunkan Angka Kematian Bayi (AKB). Bayi yang mendapat ASI ekslusif di Puskesmas Penawar Jaya tahun 2019 masih rendah, yaitu 49%. Tujuan penelitian ini untuk mengetahui hubungan antara dukungan keluarga dan pekerjaan ibu dengan keberhasilan ASI ekslusif pada bayi usia lebih dari 7-12 bulan. Jenis penelitian ini survey analitik dengan rancangan cross sectional. Sampel penelitian berjumlah 43 orang. Analisis univariat dengan persentase dan analisis bivariat dengan uji Chi Square. Hasil penelitian menunjukkan bahwa ibu yang mendapat dukungan keluarga 44,2%, ibu yang bekerja 67,4%, dan yang memberikan ASI eklusif 51,2%.  Ada hubungan antara dukungan keluarga dengan pemberian ASI eklusif (p value=0,048; OR=4,333) dan ada hubungan antara pekerjaan ibu dengan pemberian ASI eklusif (p value= 0,017; OR=6,967) pada ibu yang memiliki bayi usia lebih dari 7-12 bulan di Wilayah Kerja Puskesmas Penawar Jaya Kabupaten Tulang Bawang Tahun 2021. Saran bagi ibu bekerja agar dapat menyimpan ASI perah dan tetap memberikan ASI kepada bayi secara eklusif dengan mengikutsertakan anggota keluarga untuk mendukung pemberian ASI.